1998
DOI: 10.1021/jp9714781
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Magnetic Properties and Analysis of Valence Electronic Structures of LaT13-xAlx (T = Fe, Co) Compounds

Abstract: The magnetic properties of the LaCo13- x Al x and LaFe13- x Al x compounds have been calculated, and the valence electronic structures of these compounds have been analyzed using empirical electron theory. In general, the calculated results agree with those of the experiments. Analysis of the electronic structures reveals the relation between the electronic structures and magnetic properties of these compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…At the temperature of 2400 or so its lattice ℃ constant is a = 0.52720 nm [12] . According to the above parameter the bond names and experiment bond lengths of all the bonds in cubic zirconia which can not be neglected can be given as the following: The number of equivalent bonds of the bonds can be calculated with the formula [5][6][7][8] M S K , I I I I α =…”
Section: Ves Of Cubic Zirconiamentioning
confidence: 99%
See 1 more Smart Citation
“…At the temperature of 2400 or so its lattice ℃ constant is a = 0.52720 nm [12] . According to the above parameter the bond names and experiment bond lengths of all the bonds in cubic zirconia which can not be neglected can be given as the following: The number of equivalent bonds of the bonds can be calculated with the formula [5][6][7][8] M S K , I I I I α =…”
Section: Ves Of Cubic Zirconiamentioning
confidence: 99%
“…With the empirical electron theory in solids and molecules (EET) [5][6][7][8] , Liu Zhilin and his colleagues calculated the VES of many phase structures in ferrous alloys such as austenite, martensite, cementite and special carbide containing various alloying elements. On that basis they established the C-Me segregating theory in solid alloys [9,10] and explained many phenomena in alloys related to phase transformation such as austenite stabilization, phase transformation toughening, the influences of alloying elements on the TTT curve of phase transformation dynamics, and the influences of alloying elements on the morphology of phase transformation products.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have been studying the practical application of the EET for over 30 years. The research results about EET can be found in detail in [22][23][24][25][26][27][28]. The VES of inter-metallic compound and cast iron were analyzed [29][30][31], the calculation of the lattice constant of solids and the yield strength in some steels [32][33][34] were given, and the theoretical basis for the chemical composition design of titanium alloys was provided [35] using the VES parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Normally the results could only explain some experimental phenomena, and are opposite to some experiment facts [9] . In this paper, the relative electron density differences between the different crystal planes of silicon substrate and those of the films are calculated with the empirical electron theory in solids and molecules (EET) [9][10][11][12] . The influence of the electron density on the orientation of the texture of the films is also discussed in order to predict the orientation of the texture and heteroepitaxy of the films.…”
Section: Introductionmentioning
confidence: 99%